Inclusion of the Sustainable Development Goals in the Curriculum of Primary and Secondary Education in rural Schools of Zaragoza - Belén Dieste; Teresa Coma; Ana Cristina Blasco-Serrano (Universidad Autónoma de Madrid, 2019)
Education cannot be kept out of social and political reality. It is a fact that the current world scenario is having a considerable impact on the redefinition of the concept of Education. Global Citizenship Education (gced) implies adapting the elements of the curriculum to promote the development of values of equity and justice in the teaching-learning processes. This article analyzes, the incorporation of the gced and the Sustainable Development Goals (sdg) in the academic curriculum, as well as the dynamics and actions that are carried out in the centers and in the classrooms. A quantitative methodology has been used, developing a non-experimental descriptive study through a social survey. The results show how educational centers, are committed to introducing actions related to the gced and/ or the sdgs into their center projects. The study shows the lack of experiences involving cross-cutting and global projects and the introduction of the sdgs in a more explicit manner.